Auditoria regular realizada a las instituciones educativas del municipio de Córdoba (2), Filandria (4) y Pijao (1) para la vigencia 2012 (2013)
The development of this internship seeks to carry out regular auditing to the educational institutions of the municipality of Córdoba (2), Filandia (4) and Pijao (1) for the term 2012, on the basis of the Guide audit Territorial (GAT) issued by the Comptroller General of the Republic. Performing covers each of the phases of audit such as planning where it will be known and verified the information rendered in physical environment and through application SIA and COVI, making processes that allow establish faults that arise in the information supplied and then continue with the implementation phase. Implementation phase corresponds to lifting, confirmation and verification of information concerning the educational institutions so that it can establish and verify in a timely manner the fulfilment of each of the guidelines designed by the educational institutions framed in the performance under a legal framework.